Penghindaran Pajak Ditinjau dari Profitabilitas, Leverage, Ukuran Perusahaan dan Komisaris Independen - Dinda Asmi Marfu'ah; Kartika Hendra Titisari; Purnama Siddi (Ekonomis: Journal of Economics and Business, 2021)
Tax avoidance is a tax avoidance strategy carried out by taxpayers in a legal and safe manner and does not conflict with tax laws. The purpose of this study was to determine the effect of profitability, leverage, company size and independent commissioners on tax avoidance. The research population is Food and Baverage companies listed on the IDX in 2016-2019. Sampling using purposive sampling method obtained a sample of 11 companies with an observation period of 4 years so that a total of 44 samples. Based on multiple linear regression analysis, it is found that profitability and company size have an influence on tax avoidance. Meanwhile, the leverage variable and independent commissioner do not have an effect on tax avoidance.